Notes on the coral reef transplantation project at pristine beach in Puerto Princesa, Palawan - Regoniel, Patrick A.; Abelson, Avigdor (2015)
This report presents the initial findings of an exploratory dive in the on-going coral transplantation project site of the Department of Science and Technology (DOST). The Sangkalikasan Producers Cooperative (SPC) serves as the implementing non-governmental organization. The coral transplantation site shows reasonably good reef cover despite human pressures derived from its proximity to densely populated urban communities. The transplantation site has a structurally complex substratum able to support a high fish biomass. However, predatory fishes are few indicating overfishing among other pressures. A recent storm dislodged some transplanted corals but more than half of the transplanted corals captured on the camera survived.
Keywords: Coral reefs and islands; Coral transplantation; Sangkalikasan Producers Cooperative